Aktivitas Nano Spray Gel Ekstrak Kulit Nanas (Ananas comosus L.) terhadap Pertumbuhan Bakteri Staphylococcus epidermidis pada Ulkus Diabetes Melitus Secara In Vitro - Jesiska Muaratan; Astriani Natalia Br Ginting; Rena Meutia; Nerly Juli Pranita Simanjuntak (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Diabetic ulcers are complications of diabetes mellitus often associated with bacterial infections like Staphylococcus epidermidis. Pineapple peel is rich in secondary metabolites including flavonoids with potential antibacterial effects. This study aimed to assesss the antibacterial activity of nano spray gel made with pineapple peel extract against Staphylococcus epidermidis through in vitro testing. This research employed a laboratory experimental design using nano spray gel formulations at varying concentrations of 25%, 50%, and 75% of pineapple peel extract. Flavonoids, alkaloids, tannins, and saponins are confirmed by phytochemical analysis. Only the formulation with 75% demonstrated antibacterial activity effect, with an average inhibition zone of 8.61 mm (medium category). 25% and 50% formulations show no inhibition. Pure extract showed a 15.42 mm zone (strong), while the positive control (clindamycin) produced 29.69 mm (very strong) inhibition zone. PSA results indicated particle size averaged 1480 nm, exceeding the nanoemulsion standard (<500 nm). Nano spray gel with 75% pineapple peel extract demonstrated antibacterial activity against S. epidermidis, although the particle size did not meet nanoemulsion criteria.